Augmented wound healing potential of photosensitive GelMA hydrogel incorporating antimicrobial peptides and MXene nanoparticles - Liang, Chengzhi; Wang, Hongyu; Lin, Zhihao; Zhang, Chengdong; Liu, Guoming; Hu, Yanling (Frontiers in Bioengineering and Biotechnology, 2023)
Wound healing is a delicate and complex process influenced by many factors. The treatment of skin wounds commonly involves the use of wound dressings, which remain a routine approach. An ideal dressing can provide protection and a suitable environment for wound surfaces by maintaining moisture and exhibiting good biocompatibility, mechanical strength, and antibacterial properties to promote healing and prevent infection.The objective of this study was to design antibacterial and tissue-restorative materials for wound dressing. We encapsulated tick-derived antibacterial polypeptides (Os) as a model drug within a methylacrylyl gelatin (GelMA) hydrogel containing MXene nanoparticles. The prepared composite hydrogels were evaluated for their wound dressing potential by analyzing surface morphology, mechanical properties, swelling behavior, degradation properties, antibacterial activity, and cytocompatibility.The results demonstrated excellent mechanical strength, swelling performance, degradation behavior, and antibacterial activity of the prepared composite hydrogels, effectively promoting cell growth, adhesion, and expression of antibacterial peptide activity. A full-thickness rat wound model then observed the wound healing process and surface interactions between the composite hydrogels and wounds. The composite hydrogel significantly accelerated wound closure, reduced inflammation, and sped epithelial formation and maturation.Therefore, incorporating antibacterial peptides into GelMA provides a feasible strategy for developing excellent antibacterial wound dressings capable of tissue repair. In conclusion, this study presents a GelMA-based approach for designing antibacterial dressings with strong tissue regenerative ability.